2018
DOI: 10.3748/wjg.v24.i16.1812
|View full text |Cite
|
Sign up to set email alerts
|

Compared efficacy of preservation solutions on the outcome of liver transplantation: Meta-analysis

Abstract: AIMTo compare the effects of the four most commonly used preservation solutions on the outcome of liver transplantations.METHODSA systematic literature search was performed using MEDLINE, Scopus, EMBASE and the Cochrane Library databases up to January 31st, 2017. The inclusion criteria were comparative, randomized controlled trials (RCTs) for deceased donor liver (DDL) allografts with adult and pediatric donors using the gold standard University of Wisconsin (UW) solution or histidine-tryptophan-ketoglutarate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
0
20
0
2
Order By: Relevance
“…The most important factor affecting success of organ transplantation is protecting against ischemia-reperfusion (I/R) injury and ensuring continued organ viability [8]. With the aim of reducing organ metabolism, subjecting the organ to cold ischemia is an important method to increase viability and posttransplantation success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important factor affecting success of organ transplantation is protecting against ischemia-reperfusion (I/R) injury and ensuring continued organ viability [8]. With the aim of reducing organ metabolism, subjecting the organ to cold ischemia is an important method to increase viability and posttransplantation success.…”
Section: Discussionmentioning
confidence: 99%
“…The most common of these include University of Wisconsin (UW) solution, histidine-tryptophan-ketoglutarate (HTK), Celsior (CS), Institut Georges Lopez (IGL-1) Collins, Euro-collins, UW-PEG, Polysol, Kyoto, New Kyoto etc. [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…UW was used herein as it remains the leading solution used worldwide and has shown to remain on par with the other solutions in terms of organ protection [ 23 ]. Unfortunately, UW is not adapted for cell preservation at 37°C; this condition was thus tested for the sake of thoroughness but could not be used to test the effect of temperature.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of Szilagyi et al concluded that UW, HTK and IGL-1 solutions are associated with nearly equivalent outcomes. [31] Subgroup analyses could not identify any differences between IGL-1 and UW or HTK for primary non function and overall graft survival after one year. Some caution is warranted as only 5 studies were available for inclusion in this systematic review and therefore no firm conclusion can be drawn.…”
Section: Plos Onementioning
confidence: 94%